The effectiveness of consumer-oriented food subsidies in reaching rationing and income transfer goals - Pinstrup-Andersen, Per; Alderman, Harold (International Food Policy Research Institute, 1988)
The goals of consumer food subsidies vary among countries and over time. Analyses of food subsidies in a number of countries reveal that one or both of two goals are commonly found. These are (1) to assure that all or certain groups of households—frequently urban ones—have access to a specified minimum quantity of staple foods at "reasonable" prices, and (2) to transfer incomes to certain population groups through lower food prices or food stamps. In this chapter these two goals will be referred to as rationing and income transfer.